World water '86 water technology for the developing world : proceedings of an international conference organised by the Institution of Civil Engineers and held in London on 14-16 July 1986. (Thomas Telford, 1987)
These papers focus on water resources management and safeguarding water quality, forecast the supply and demand of water, and highlight new developments in surface irrigation and horizontal drainage.